THE EFFECT OF PLANTATION ESTABLISHMENT METHOD AND ATONIK APPLICATION IN GOLDENROD (Solidago virgaurea L. ssp. virgaurea) CULTIVATION - Barbara Kołodziej (Acta Scientiarum Polonorum: Hortorum Cultus, 2008)
In four-year-lasting field experiment yielding and chemical composition of goldenrod (Solidago virgaurea L. ssp. virgaurea) herb depending on different methods of plantation establishment and natural growth regulator Atonik application were analysed. In the experiment different methods of goldenrod plantation establishment were compared: A. direct spring diaspores sowing, B. spring planting of seedlings, C. direct autumn diaspores sowing, D. autumn planting of seedlings as well as spraying with 0.1% solution of Atonik twice a year. Diaspores were sown directly onto the field in rows 40 cm apart, whereas seedlings were produced in multicell trays in plastic tunnel throughout 5 weeks and then transplanted onto the field in 40 cm × 15 cm raw spacing. Raw material was harvested every year at the beginning of blooming stage and after that chemical analyses comprised leiocarposide content (by HPLC method) were done. The highest yields of raw material were obtained in the second and third years of cultivation, while in the fourth year a considerable yields decrease was observed, indicating that goldenrod plantation should last two or three years. Higher raw material yields characterized by higher leiocarposide content were collected from the plots with spring seedlings transplanting or autumn diasporas sowing, thus these methods of plantation establishment should be recommended on commercial plantations of goldenrod. Additionally, plants should be sprayed with 0.1% Atonik in order to increase raw material yields.